The Effect of Pre Service EFL Teachers Deeper Learning Awareness on the 21st Century Skills Promotion - Sukarno Sukarno; Dwiyani Pratiwi (English Education Department, 2025)
The current study aims to investigates the effect of pre service EFL teachers awareness of promoting deeper learning on students 21st century skills encouragement This quantitative research uses a cross sectional survey design The participants were 366 pre service EFL teachers from five universities in the Special Region of Yogyakarta Indonesia The data were collected by distributing two questionnaires: the Deeper Learning Awareness adapted from Jiang 2022 and Rodriguez and Fitzpatrick 2014 and the 21st Century Skills questionnaires adapted from Kelley et al 2019 The pilot testing expert judgement and SPPS analysis were used to assess the questionnaires validity reliability and practicality The data were analyzed using Regression Analysis The result reported that pre service EFL teachers in the Special Region of Yogyakarta are aware of promoting deeper learning to support students 21st century skills Their deeper learning awareness also significantly predicted the promotion of 21st century skills The more pre service EFL teachers are aware of promoting deeper learning the more the 21st century skills are implemented in the EFL learning < p>